Novel production method of porous surface Ti samples for biomedical application - Reis de Vasconcellos, Luana Marotta [UNESP]; Oliveira, Fernanda Nascimento [UNESP]; Leite, Daniel de Oliveira [UNESP]; Oliveira de Vasconcellos, Luis Gustavo [UNESP]; do Prado, Renata Falchete [UNESP]; Ramos, Carolina Judica [UNESP]; de Alencastro Graca, Mario Lima; Alves Cairo, Carlos Alberto [UNESP]; Carvalho, Yasmin Rodarte [UNESP] (Springer, 2012)
A porous implant material with adequate pore structure and the appropriate mechanical properties for bone ingrowth has long been sought. This article presents details of the development, characterization and in vivo evaluations of powder metallurgy-processed titanium samples exhibiting a dense core with an integrated porous surface for biomedical applications. A space-holder method was applied to investigate the effects of different percentages and particle sizes of the urea on bone neoformation in 30 rabbits. The samples were previously characterized using scanning electron microscopy and mechanical testing. After 8 and 12 weeks of implantation, bone ingrowth was histologically and histometrically analyzed and push-out testing was performed. This study demonstrated that the association of a dense core integrated with the greatest number of interconnected pores of the smallest size is a promising biomaterial for bone tissue engineering. This sample exhibits appropriate mechanical properties combined with increased bone ingrowth, providing enhanced resistance to displacement.